Penerapan Perjanjian Akad Mudharabah Muqayyadah Dalam Skema Pembiayaan Perspektif Hukum Islam (Studi Kasus Di KJKS BMT-UGT Sidogiri Cabang Pembantu Banyuputih) - Muhammad Rosid (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
Implementation of the Akad Mudharabah Muqayyadah Agreement in the Islamic Law Perfektif Financing Scheme Case Study at KJKS BMT-UGT Sidogiri Branch Of Banyuputih Situbondo Maid. The purpose of this study is to determine if the principles of the muqayyadah mudharabah agreement at the Baitul Maal wat Tamwil Islamic Financial Services Cooperative (KJKS BMT-UGT Sidogiri) banyuputih auxiliary branch comply with Islamic sharia. and the elements that lead to the promise being broken (wansprestasi) in the funding of this mudharabah, as well as how to fix it. Using Primary and Skunder.data data sources, this study adopts a combination doctrinal (normative) and empirical (non-doktrial) approach of combining. Data collection techniques include conducting interviews, observations, and literature studies, followed by data analysis techniques using qualitative analysis. Secondary legal materials include primary, secondary, and tertiary legal materials, as well as primary, secondary, and tertiary legal materials. The values contained in the principles of the mudharabah agreement on Baitil Maal wat Tamwil (BMT) Sidogiri Capem Banyuputih in mudharabah financing products have been found to be in accordance with Islamic law, because the principles of the mudharabah agreement akad mudharabah, based on (al-mabadi al-ammanah), namely the value of justice (al-i) have been implemented (at tasamuh). Inadequate human resources, management of Islamic financial institutions, information systems and technology, and the lack of moral standards set in financing activities are the elements that lead the mudharabah agreement to be broken. Then mastering the technical components, philosophical law of Sharia economy, and sharia economic law is a solution. In the event of a breach of the agreement, the peace system (sulhu) of the arbitration court (tahkim) and the legal process are used to address the situation (al-qadha). Keywords: Financing; Mudharabah.